Synthesis, Structure, and Catalytic Activity of Tridentate, Base‐Functionalized β‐Ketiminate Zinc Complexes in Ring‐Opening Polymerization of Lactide. Issue 13 (25th March 2014) - Scheiper, Christoph; Dittrich, Dennis; Wölper, Christoph; Bläser, Dieter; Roll, Joachim; Schulz, Stephan
Abstract: Zinc complexes [LZnR] containing tridentate β‐ketiminate ligands with an additional side‐arm donor {referred to as [NNO] ligands; L =L 1 = OC(Me)C(H)C(Me)NCH2 CH2 CH2 NMe2, R = Me (1 ), Et (2 ), Cl (3 ); L =L 2 = OC(Me)C(H)C(Me)NCH2 CH2 NMe2, R = Me (6 ), Et (7 ), Cl (9 )} as well as cationic derivatives with a weakly coordinating anion [LZn][Al(OC(CF3 )3 )4 ] [L =L 1 (4 ), L =L 2 = (10 )], a base‐stabilized complex [L 2 Zn(dmap)Et] (8 ; dmap = 4‐(dimethylamino)pyridine), and a base‐free complex without a side‐arm donor [L 3 ZnEt] [12, L 3 = OC(Me)C(H)C(Me)N‐2, 6‐ i Pr2 C6 H3 ] were synthesized and characterized by single‐crystal X‐ray diffraction (1, 2, 3, 8, 9, 11, and12 ). The ring‐opening polymerization (ROP) of rac ‐lactide was studied with the zinc complexes1 –4, 6 –10 and12, mixtures of7 and Lewis bases [7 /1, 8‐diazabicycloundec‐7‐ene (7 /DBU;15 ), 7 / t BuPy (16 )], and12 /DBU (17 ). Lithium‐β‐ketiminatesL 1 Li (5 ), L 2 Li (11 ), DBU (13 ), and a mixture ofL 2 Li/DBU (14 ) were also investigated. All compounds except for3, 4, 10, and12 are active rac ‐lactide polymerization catalysts by a slightly modified activated‐monomer mechanism. The catalytic activity of the complexes in rac ‐lactide polymerization reactions at ambient temperature increases with the addition of Lewis bases to the β‐ketiminate zinc compounds. The highest activity was found for the mixture7 /DBU (15 ), which converted 200 equiv. of rac ‐lactide into polylactide within 1.5 min at ambient temperature. Abstract : Several NNO zinc complexes were synthesized and structurally characterized by single‐crystal X‐ray diffraction. In addition, their catalytic activity in the ring‐opening polymerization (ROP) of lactide is presented. The polymerization occurs through a modified activated‐monomer mechanism.